Importance of Education for Expectant Mothers - Muhammad Ma’ruf Ch (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2012)
Not many people talk about the role of a mother. But they acknowledgethat we are in world to the mother because. Actually, children are a source ofgreat joy and delight, they make life sweet, bring more rizq into a family’s lifeand give hope. A father sees his children as a future source of help and support,as well as representing an increase in numbers and perpetuation of the family.A mother sees her children as a source of hope, consolation and joy in life, andas hope for the future. All of these hopes rest on the good upbringing of thechildren and giving them a sound preparation for life, so that they will becomeactive and constructive elements in society, a source of goodness for their parents,community and society as a whole. Then they will be as Allah Subhanahu wata’ala described them: “ Wealth and sons are allurements of the life of thisworld . . .” (Qur’an 18:46).If their education and upbringing are neglected, they will become badcharacters, a burden on their family, community and society as a whole. Onlywaiting the Muslim woman’s sincerity, how to manage the great responsibilityfor forming their resource, especially in character building1. And how is theMuslim women have understanding the great responsibility and use the bestmethods in bringing them up, and do they able to demonstrate their love andaffection, also treat their sons and daughters equally, even they do not discriminatebetween sons and daughters of their affection, in other time the Muslim womenalert to everything, that may have an influence on their children they instill goodbehavior and attitudes in them.